The Fog of War: Russia’s War on Ukraine, European Defence Spending and Military Capabilities - Daniel Fiott (Intereconomics)
Abstract Some … may look at the depleted nature of Russia’s military after its invasion of Ukraine and incorrectly surmise that defence spending increases are not that necessary after all.